Evaluating the product portfolio of Japanese public service broadcaster: Consumer vs. citizen's view - Masatsugu Tsuji; Yoshiharu Ichikawa (International Telecommunications Society (ITS), 2014)
Media has been becoming increasingly diversified and public service broadcasters (PSBs) all over the world face new challenges by the Internet, and they have been restructuring their consistencies for the new environments. PSBs have been developing various management approaches by the diversification of transmission channels and the development of cross-media contents. The optimum deployment of distribution channels and content genres is currently becoming the top management priority, which is referred to as Portfolio Management. This approach for determining the portfolio of products and businesses will result in the most efficient strategic allocation of management resources. This paper thus takes NHK (Nippon Hoso Kyokai), Japan's PSB, as a research target, and analyzes its portfolio management. NHK has introduced the VFM (Value for Money) index through the measurement of WTP(Willingness to pay), and has initiated channelgenre matrix management. This study thus aims to estimate WTP to the channelgenre matrixin order to analyze how viewers evaluate NHK and its programs. To evaluate whether NHK's channelgenre matrix management is oriented to the way as pay-TV or to public service value, PSM (Propensity Score Matching) is employed. Using PSM, the sample population is divided into two groups, the consumer's view and the citizen's view, and how the distributed WTP to genre is different between two groups is examined.
Keywords: 330; WTP; product portfolio; channel-genre matrix; PSM; NHK